2004
DOI: 10.1007/s00586-004-0712-6
|View full text |Cite
|
Sign up to set email alerts
|

Back pain in pregnancy: 1-year follow-up of untreated cases

Abstract: IntroductionBack pain (BP) is one of the most frequent symptoms to appear during the last period of pregnancy and a high incidence has been described in several studies [2,6,7,9,14,17]. Since 1984 modern studies of BP also need to include patient-oriented assessment [23]. Self-administered questionnaires are the most common instruments to assess patient perspective in evaluating the clinical picture, and the usefulness of these instruments [20, 21] is widely accepted. BP during pregnancy has been quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
(39 reference statements)
1
18
0
2
Order By: Relevance
“…Reported prevalence of back pain 1 to 6 years after pregnancy varies between 16 and 51% [2][3][4][5], and studies have reported that between 35 and 76% of pregnant women experience back pain [3,[5][6][7][8][9][10]. A recent systematic review of pregnancy-related lumbopelvic pain estimated prevalence to be 45.3%, with a reported range of 3.9 to 89.9% from studies considered to be of acceptable standard [11].…”
Section: Introductionmentioning
confidence: 99%
“…Reported prevalence of back pain 1 to 6 years after pregnancy varies between 16 and 51% [2][3][4][5], and studies have reported that between 35 and 76% of pregnant women experience back pain [3,[5][6][7][8][9][10]. A recent systematic review of pregnancy-related lumbopelvic pain estimated prevalence to be 45.3%, with a reported range of 3.9 to 89.9% from studies considered to be of acceptable standard [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lumbopelvic pain usually resolves after delivery. However, 51% of women with pain during pregnancy report experiencing LBPP 1 year postpartum (10), and 20% of women report LBPP 3 years postpartum (11). It has been shown that a higher intensity of pain experienced during pregnancy indicates a worse prognosis after delivery (12).…”
mentioning
confidence: 99%
“…Disability in lumbar pelvic pain during pregnancy ranges from 21-81% median 28%. 17 It has been proposed that due to increased weight gain in pregnancy, shifting of the centre of gravity of the body anteriorly and stretching the abdominal muscles of accommodation the enlarging uterus causes muscle fatigue. In India the cultural habits of squatting, sleeping on flat firm surface is common; This maintains the spine in physiological position and may contribute to spontaneous realignment of minor malalignments of lumbo-pelvic joints.…”
Section: Resultsmentioning
confidence: 99%